The effectiveness and risks of loose monetary policy under financialisation - Sara Feiner Solís (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper incorporates low interest rates into a framework of Post-Keynesian theory of the firm under financialisation and uses Compustat data to provide an empirical analysis of firm behaviour in the Eurozone for the period 2000-2018. It reasons that loose monetary policy targeting low interest rates will only be effective in promoting investment in a scenario where shareholder value orientation (SVO) tightens the finance constraint on growth-maximising managers. In contrast, when shareholder value maximisation becomes the goal of the firm, loose monetary policy may not only be ineffective in promoting growth, but might actually be dangerous because it fosters financial fragility and promotes SVO. Data suggest that financialisation in the Eurozone represents a shift in the objectives of the firm towards maximising free cash flows. There is no evidence that loose monetary policy fostered leverage and an equity reduction in the Eurozone, which might be a consequence of its institutional context and ownership structures. Still, the analysis shows that low interest rates were largely ineffective in fostering investment during the period 2008-2018. Therefore, monetary policy seems insufficient to promote investment and growth. Both expansionary fiscal policy and legal reforms that control shareholder power are needed.
Keywords: D21; D22; G30; 330; financialisation; shareholder value orientation; investment theory